Marxism and Laughter The Places of Laughter and their Intellectual Implications in the Texts of Marx and Engels - علي هلا; المحمد محسن (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research is concerned with tracing and identifying the places of laughter in the texts of Marx and Engels, and at the same time revealing their implications that may contribute to viewing the Marxist text from an angle that reveals the intellectual dimensions of Marxist criticism. This research also seeks to explain why the satirical critical character prevailed over many critical texts that establish the materialistic conception of history. Simultaneously, it reveals the close connection between laughter in the Marxist text and the ideology that Marx recognized- in his book “The German Ideology- that it belongs either to a distorted conception of history or to a total suspension of it. In short, this approach aims to answer the following question: "When does a Marxist laugh?"